Impact of Sphingolipid Mediators on the Determination of Cochlear Survival in Ototoxicity - Tabuchi, Keiji; Hara, Akira (Current Molecular Pharmacology, 2018)
Background and Objective: Sphingolipid metabolites, including ceramide, sphingosine, and their phosphorylates (ceramide-1-phosphonate [C1P] and sphingosine-1-phosphate [S1P]), regulate diverse cellular processes including apoptosis, the cell cycle, and cellular differentiation. Recent studies have shown that these sphingolipid metabolites are generated in response to ototoxic agents and play important roles in determining the fate of cochlear hair cells in ototoxic injury. Methods: This review summarizes the current knowledge on the roles of sphingolipid mediators in cochlear ototoxicity. Results: During ototoxicity, ceramide is mainly generated via sphingomyelinase in the cochlea through a ceramide/sphingomyelin cycle from sphingomyelin. The generated ceramide is converted to other sphingolipid mediators. Ceramide and sphingosine accelerate cochlear hair cell death induced by ototoxic agents, while, C1P and S1P, on the other hand, protect cochlear hair cells. Hair cell protection of S1P is mediated by S1P receptor subtype 2 (S1PR2). Conclusion: Sphingolipid mediators play important roles in cochlear hair cell survival or death in ototoxic injury.
Keywords: ceramide